I Draw Therefore I Am: Drawing as Visual (Communication) Studies - Muliyadi Mahamood; Karna Mustaqim (ITB Journal Publisher, LPPM ITB, 2013)
This paper sets view to consider the significance of drawings as part of visual communication design. Drawing gives a chance to observe, to muse, to select and develop continuous thinking techniques. It is to present that drawing is not just a cursory to generate ideas, but it has its own energy and philosophy which deserve studying as a domain of art. In recent years, drawing has received attention; there is on the one hand a group of drawing practitioners, and on the other hand a group of drawing researchers. Drawing in design is a medium of visual and spatial thinking. Digging into research actually is a necessity for visual communication studies. It is suggested here three kinds of research approaches: research into art/design; research through art/design; and research for art/design. Indeed, it leads to four axis topics (topoi) for design studies: design practice, design product, design discourse, and design meta-discourse. A field of study called 'visual culture' which, departed from the study of critical theory and cultural studies which have set out relatively new field of study called 'visual studies'. Based upon to this perspective, visual (communication) studies should be more self-reflexive. The production of visual communication contributes to construct the visual culture in society.